An unusual case of Candida parapsilosis endocarditis of the native tricuspid valve secondary to a tunneled dialysis catheter - Zacarías Mendoza, Nathalie Victoria (2023)
Candida endocarditis is a severe disease associated with high mortality rates. Candida parapsilosis is frequently identified as the causative pathogen in intravenous drug users and is commonly associated with nosocomial infections, primarily due to its ability to form biofilms on catheters or other foreign bodies. Here, we present a rare case of Candida parapsilosis endocarditis affecting the native tricuspid valve in a 35-year-old male patient with end-stage chronic kidney disease (Stage V), who had a suspected fungal infection related to the left cervical catheter. The patient received treatment with caspofungin and underwent excision of a verrucous tumor on the tricuspid valve. Despite encountering postoperative complications, the patient was discharged on fluconazole treatment and scheduled for follow-up. Candida endocarditis poses a clinical challenge that necessitates a multidisciplinary approach and tailored management due to its infrequent occurrence and higher mortality rate compared to bacterial endocarditis.